Thermal design of a double-tube heat exchanger for acetone cooling - Pérez Sánchez, A.; Pérez Sánchez, E.J. (Nexo Revista Científica, 2019)
The double-tube heat exchanger is one the simplest piece of equipment which performs heat exchange in a continuous mode between two fluids. In the present work the thermal design of a double-tube heat exchanger for the cooling of a liquid acetone is carried out. It was also evaluated the influence of the increment of acetone feed flowrate over six design parameters of the heat exchanger: 1) overall heat transfer coefficient; 2) heat transfer area; pressure drop of 3) acetone and 4) ethylene glycol streams; 5) heat exchanged and 6) total amount of hairpins needed. The heat exchanger must have a total heat transfer area of 6.0 m2 and a total amount of hairpins of 10 to fulfill the system’s thermal duty. Both the acetone and ethylene glycol streams have pressure drop values lower than the maximum allowable limit established by the process (110 000 Pa). The increment of the acetone feed flowrate causes the increment of the six parameters studied.